2015
DOI: 10.2217/epi.15.54
|View full text |Cite
|
Sign up to set email alerts
|

Altered miRNA Expression in the Cervix During Pregnancy Associated with Lead and Mercury Exposure

Abstract: Background/Aim Toxic metals including lead and mercury are associated with adverse pregnancy outcomes. This study aimed to assess the association between microRNA (miRNA) expression in the cervix during pregnancy with lead and mercury levels. Methods We obtained cervical swabs from pregnant women (n=60) and quantified cervical miRNA expression. Women’s blood lead, bone lead, and toenail mercury levels were analyzed. We performed linear regression to examine the association between metal levels and expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 53 publications
(67 reference statements)
0
30
0
Order By: Relevance
“…A lot of studies suggested that environmental metal pollutants can induce changes in miRNA expression (16)(17)(18). In our research, miRNA microarray assay and subsequent validation revealed that miR-92a and miR-486 were positively associated with mercury exposure.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A lot of studies suggested that environmental metal pollutants can induce changes in miRNA expression (16)(17)(18). In our research, miRNA microarray assay and subsequent validation revealed that miR-92a and miR-486 were positively associated with mercury exposure.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have explored the miRNAs expression profiles of general population environmentally exposed to mercury. Sanders et al (18) assessed the association between miRNA expression in the cervix with mercury levels during pregnancy and found 17 miRNAs were negatively associated with toenail mercury levels. However, few studies have investigated potential effects of occupational mercury exposure on miRNA expression profiles in plasma.…”
Section: Original Articlementioning
confidence: 99%
“…The associations between the aberration of miRNAs profiles and heavy metals exposure have been confirmed by a number of studies 15 , 16 . Our population-based study confirmed that miR-92a and miR-486 expression levels were upregulated in workers exposed to occupational mercury.…”
Section: Discussionmentioning
confidence: 70%
“…Besides alterations of DNA methylation or/and histone modifications, numerous changes in miRNA profiles have been associated with exposure to different metals, among them mercury, arsenic, and cadmium [ 146 ], and a negative correlation between mercury and lead levels and various miRNAs has been found in cervical swabs from pregnant women [ 147 ].…”
Section: Causes Of Epigenetic Changes During Development Adult LImentioning
confidence: 99%